Bridging awareness and booking behaviour: a critical analysis of sustainability and environmental certifications in Italian tourism - Giraldi, Luca; Capanna Piscè, Guido; Olivari, Luca (Piccola Impresa / Small Business, 2025)
Purpose. This study aims to explore the influence of green certifications and eco-friendly practices on holiday decisions among Italian tourists, examining whether these environmental credentials genuinely impact travel choices in the increasingly sustainability-conscious tourism sector. Design/methodology/approach. The methodology employed consisted of structured quantitative survey instruments administered to over 300 Italian respondents. Analysis included descriptive and inferential statistics, structural equation modelling (SEM) to investigate underlying causal relationships, and cluster analysis to identify distinct consumer segments. Findings. The results of the study demonstrate the pivotal function of tourism and services in the economic development of peripheral regions. There is a notable interest among young people in the advancement of these areas. Nevertheless, the analysis reveals critical concerns pertaining to mobility, inadequate infrastructure, and a paucity of cultural events and networking prospects. The aspiration to reside in these areas is frequently impeded by the perception of limited employment and business prospects. Practical and Social implications. The findings highlight a significant gap between the respondents' support for eco-friendly practices and booking behaviours. Despite broad sustainability awareness, several travellers lack a clear understanding of environmental certifications. Tourism businesses need to enhance communication about their environmental initiatives, and regulatory bodies should reassess their strategies for promoting sustainable tourism. Effective consumer education and clear communication of the benefits of sustainability certifications are pivotal. Originality of the study. This research breaks new ground by examining the dual facets of awareness levels and the influence of sustainability certifications on holiday choices. It identifies critical areas for improvement, such as better consumer education, streamlined certification communication, and targeted engagement strategies, providing valuable insights for hospitality businesses to leverage sustainability as a competitive advantage.